2007
DOI: 10.1007/bf03000185
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of medication adherence among persons living with HIV

Abstract: The data suggest that patients' beliefs about treatment are formed to a certain degree in the patients' relationship with the physician. Furthermore, adherence seems to be related to personal values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 47 publications
2
44
2
3
Order By: Relevance
“…19 The findings in this study differ slightly to those of Gauchet et al, 34 who in their French study, examined the extent to which medication adherence in HIV patients related to social and psychological variables. Although the authors found patient beliefs about medicine to relate to adherence, as found in the current study, their findings showed that the influence of beliefs about medicine on medication adherence was also mediated by the patient-provider relationship and by HIV illness or medication representation on the part of the patients.…”
Section: Resultscontrasting
confidence: 61%
“…19 The findings in this study differ slightly to those of Gauchet et al, 34 who in their French study, examined the extent to which medication adherence in HIV patients related to social and psychological variables. Although the authors found patient beliefs about medicine to relate to adherence, as found in the current study, their findings showed that the influence of beliefs about medicine on medication adherence was also mediated by the patient-provider relationship and by HIV illness or medication representation on the part of the patients.…”
Section: Resultscontrasting
confidence: 61%
“…Of the papers relating beliefs about medicines to a measure of medication adherence, some report only necessity beliefs are correlated to medication adherence [19,21,22,[35][36][37][38] while others have found only concern beliefs to be correlated to medication adherence [30,[39][40][41][42][43]. In some studies, the necessity-concerns differential was shown to have a stronger correlation with adherence than necessity or concern beliefs alone [4,20,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…However other researchers argue that long waiting times, poor staff attitudes, intermittent drug availability and other procedural barriers decrease patients' adherence to ART and also result in poor clinic attendance [19][20]. Continuous accessement to health care services and medications by patients also influences treatment adherence [19].…”
mentioning
confidence: 99%
“…Continuous accessement to health care services and medications by patients also influences treatment adherence [19]. The patient-provider relationship as emphasized by Altice et al [16] and Gauchet et al in their studies, is another factor that has been well researched in terms of adherence to ART [20]. The same authors continue to state that a good patient-provider relationship results in patient's trust and confidence in the provider which in turn influences good adherence [16,20].…”
mentioning
confidence: 99%